Penilaian Pelaksanaan Governansi Korporat pada Perumda Air Minum Tirta Sago Kota Payakumbuh - Noer, Alinursal (Jurnal Eksplorasi Akuntansi, 2024)
The purpose of this research is to identify and study good corporate governance practices at the Tirta Sago Payakumbuh Regional Public Water Company, which functions to implement the company's vision, mission, and goals, meet the expectations of relevant stakeholders, and illustrate the principles of transparency, accountability, responsibility, independence, and fairness-guidelines for implementing corporate governance. This research used a qualitative method with snowball sampling to find additional information sources. After data is collected through observation, interviews, and document analysis, analytical techniques are used to reduce, store, and draw conclusions. The research results show that public drinking water companies in the area have implemented good corporate governance practices, but not completely.